Authenticity and Cultural Value as Drivers of Customer Satisfaction in the NAJMA Handwritten Batik Lasem Industry: An SEM-PLS Approach - Lafinati Intan Suryaneta; M. Fathur Rahman (Universitas Syiah Kuala and Collaboration Yayasan Yusda Edu Indonesia, 2026)
The decline in turnover and increased competition among Batik MSMEs necessitate an understanding of the factors that influence customer satisfaction with Batik Tulis Najma. This study aims to analyse the influence of added-value product quality, customer service quality, and marketing strategies on customer satisfaction, both directly and indirectly. The study uses a quantitative approach with the Partial Least Squares (PLS) method with 106 respondents. The results show that added value, product quality, and marketing strategy have a positive effect on customer satisfaction. Service quality does not have a significant direct effect, but it does have a significant effect through added value product quality, both directly and through marketing strategy. Conversely, service quality through marketing strategy has no significant effect. These findings confirm that increasing product added value and effective marketing strategies are key to improving customer satisfaction and the competitiveness of batik SMEs.